2003
DOI: 10.1080/10413200305385
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles of Iditasport Ultra-Marathon Participants

Abstract: Each February, competitors convene in Big Lake, Alaska, to participate in the "Iditasport Human Powered Ultra-Marathon". Who would attempt this challenging race? Personality might be one factor predicting participation. Iditasport represents a unique athletic event with a distinctive social and psychological climate that might be reflected in the personalities of the participants in many ways. This study was designed to identify the personality profile of Iditasport athletes when compared to normative populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
5
32
0
1
Order By: Relevance
“…Consistent with evidence linking Openness to greater levels of experience seeking [131], this personality trait (along with extraversion) may be associated with activation of the dopaminergic system [132]. Specifically, individuals high in Openness may respond to stressors through active engagement, or by interpreting novelty as challenging or exciting rather than threatening.…”
Section: Openness To Experiencementioning
confidence: 64%
“…Consistent with evidence linking Openness to greater levels of experience seeking [131], this personality trait (along with extraversion) may be associated with activation of the dopaminergic system [132]. Specifically, individuals high in Openness may respond to stressors through active engagement, or by interpreting novelty as challenging or exciting rather than threatening.…”
Section: Openness To Experiencementioning
confidence: 64%
“…Our findings generally support these conclusions and, by providing some detailed examples of the nature of stressors and coping strategies, serve to create a more complete explanation of psychological factors associated with ultramarathon running. Hughes et al (2003) suggested future research should look at how people "change as a result of participation [in ultramarathons]" (p. 260). We provided two examples-Ted's admission it was the hardest thing he had ever done in his life and Richard's reference to teaching himself a lesson-that indicate ultramarathoning running may provide opportunities for growth.…”
Section: Discussionmentioning
confidence: 97%
“…But whereas some distinct demographic and training factors are associated with ultramarathon runners, studies have failed to clearly demonstrate personality traits that predispose individuals to participate in ultramarathons. For example, in a study of 54 participants in the Iditasport (foot) ultra-race in Alaska, compared with a normative sample, participants scored higher on personality traits such as extraversion and experience seeking (Hughes, Case, Stuempfle, & Evans, 2003). However, no significant differences were found between athletes and the norm group on traits of neuroticism, agreeableness, contentiousness, boredom susceptibility, or thrill/adventure seeking.…”
mentioning
confidence: 95%
“…Conformity (Thatcher et al, 2003) and mastery (Slanger & Rudestam, 1997) are also important and must not be overlooked. These differences may well be explained by looking at the differences between the sports studied (Delle-Fave, Bassi & Massimini, 2003;Hughes, Case, Stuempfle & Evans, 2003;Thatcher, Reeves, Dorling & Palmer, 2003). The critical difference between polar exploration and the more risky sports of surfing, skydiving, snowboarding, sailboarding and extreme skiing, which are more explosive and short-lived (Kerr, 1999) may give us a clue about the types of motivations we would expect to find.…”
Section: A Framework For Studying Motivationmentioning
confidence: 99%